Autologous full-thickness skin graft for treating squamous carcinoma in a patient with psoriasis. Issue 39 (25th September 2020) - Zhang, Guiyun; Bu, Wenbo; Wang, Shuang; Li, Xue; Wang, Shu; Li, Fuqiu; Yao, Chunli
Abstract : Abstract: A 31-year-old male patient with psoriasis received administration of traditional Chinese medicine (TCM) during a disease course of 14 years. He showed multiple keratoma together with squamous cell carcinoma (SCC) in left lower limbs. After admission, the conditions were stable after treatment, and received surgery for treating SCC. The skin defect was treated using full-thickness skin graft. The postoperative survival of the flap was satisfactory, and the conditions of psoriasis were well controlled. In this case, we presented the feasibility of graft in the donor site from a psoriatic lesion. Besides, we analyzed the possibility of SCC and keratinizing lesions.